Pengaruh Return On Assets, Leverage, Corporate Governance, Ukuran Perusahaan dan Kompensasi Rugi Fiskal pada Tax Avoidance (Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2013) - Rachmithasari, Annisa Fadilla; , Dra. Mujiyati, M.Si (2015)
Tax Avoidance is a strategy to do legally with tax evasion does not violate the rules of taxation. This research aims to test the influence of Return On Assets (ROA), Leverage (LEV), independent Commissioner (KOM), Audit Committee (AUD) Perusahaani, size (SIZE), and the fiscal Loss Compensation (RFIS) against Tax Avoidance (Y). The population of this research is the entire manufacturing company registered in indonesia stock exchange (BEI ) 2011-2013 during the period .A method of sampling nonprobability using methods with techniques of sampling purposive sampling .The technique of analysis of data using the test is the classic multikolinieritas , autokorelasi test , test and test heteroskedastisitas normality .Testing the hypothesis of the use of regression analysis double. The results of research concluded that: return on assets not impact on tax avoidance evidenced by the coefficients of beta 0,094 and 0.338 of a significant degree , leverage positive influence on tax avoidance evidenced by the coefficients of beta 0,332and 0,001 a significant degree , independent commissioner bepengaruh negative against tax avoidance evidenced by the coefficients of beta -0,195 and 0,045 of a significant degree , audit committee have negative effects on tax avoidance evidenced by the coefficients of beta -0,319 and 0,001 of a significant degree , the size of the company has no impact on tax avoidance evidenced by the coefficients of beta -0,088 and 0,363 of a significant degree , compensation for loss of fiscal not impact on tax avoidance evidenced by the coefficients of beta 0,040 and 0,675 of a significant degree